Community Stakeholders’ Perspectives of Craft Breweries in Their Communities in Oklahoma - Cara Jolly; Quisto Settle; Laura Greenhaw; Ruth Inman; Dwayne Cartmell (Journal of Applied Communications, 2021)
Craft breweries are a growing industry in the United States, including Oklahoma. Craft breweries have unique characteristics that affect their brands. One of those characteristics is craft breweries’ tie to their local communities through place branding and serving as a third space (i.e., not home or work) for community members. Interviews were conducted with community stakeholders in Oklahoma to understand how the stakeholders perceived the brands of breweries in their communities. Results of the interviews indicated that craft breweries were positively received by communities. Participants believed the breweries were valuable to the local community by contributing to existing culture and fostering connections between community members. The participants also believed brewery personnel were positively engaged in their communities and other businesses, as well as engaging in socially conscious actions. The participants indicated that craft breweries enhanced credibility and tourism of communities. Community leaders should be aware of the potential contribution craft breweries for the cities. This includes aiding tourism, improving attractiveness of the city for those looking to relocate, and fostering interactions between community members. Community leaders and craft brewery owners should be aware of the added value of using place branding via local community ties. In other words, the brewery benefits from tying itself to the community while also adding value to the community. Future research should assess if these results apply to craft breweries in other states. Future research should also address consumers’ perspectives of how breweries use community ties and how craft breweries influence tourism.
Keywords: craft breweries; place branding; third space; social capital; coopetition